THE CONCEPT OF MORAL EDUCATION ACCORDING TO IMAM AL GHAZALI AND RELEVANCE TO EDUCATION IN INDONESIA - Syaiful, Mohammad; Anam, Rifqi Khairul (Universitas Muhammadiyah Metro, 2024)
Education serves as a catalyst for profound transformation by addressing individual foundations, since it has the capacity to dismantle the edifice of ignorance.sectioned logically as an overview of what appears in the paper. Imam al-Ghazali emphasized the need of maintaining equilibrium between the temporal world and the hereafter. He asserted that moral education extends beyond theoretical concepts and must be shown in daily practice. Imam al-Ghazali's perspectives on moral education remain pertinent to contemporary youth. This research is study literature, particularly in academia, aimed at advancing theoretical frameworks and practical applications. The result is Imam Al-Ghazali sees moral education as an all-encompassing character development process, including both formal and informal elements. Non-formal education originates inside the family, while formal education includes educators who function as diagnosticians and givers of solutions. The primary objective of moral education is to attain satisfaction in both this life and the hereafter, while cultivating persons of virtuous character.Pendidikan berfungsi sebagai katalisator transformasi pribadi dan masyarakat. Islam, khususnya melalui ajaran Imam al-Ghazali, memberi penekanan signifikan pada pendidikan moral. Penelitian ini menyelidiki konsepsi Imam al-Ghazali tentang pendidikan moral dan relevansinya dengan praktik pendidikan kontemporer. Melalui tinjauan pustaka yang komprehensif, studi ini meneliti pendekatan al-Ghazali yang beragam terhadap pengembangan moral, yang meliputi pemurnian diri, tanggung jawab sosial, dan pertumbuhan spiritual. Temuan ini menyoroti signifikansi abadi dari ide-ide al-Ghazali dalam mengatasi tantangan moral kontemporer. Dengan memahami dan menerapkan prinsip-prinsip al-Ghazali, para pendidik dapat menumbuhkan individu-individu dengan karakter dan kompas moral yang kuat, yang berkontribusi pada perbaikan masyarakat.